Export Of Malaysia Business-To-Business Services: An Examination Of Civil Engineering Consultancy - Law , Yuk Hui (2010)

(untitled)
The surplus of balance of payment in the services sectors for the first time in 2007 portends the services sector becoming the main economic contributor to Malaysia, overtaking the industrial sector. Among the business-to-business services, engineering services is the most impressive. Among the 86 disciplines in engineering services, civil engineering has the highest number of registered engineers (i.e. 47.4% for 1986-2006 periods). A study was conducted to examine the export of Malaysia’s business-to-business services, notably civil engineering consultancies. Data was collected from postal questionnaire survey, face-to-face interviews and secondary sources.